(untitled) (Veterinary Science, 2021)
The objective of this work was to determine the frequency and characteristics of the behavioral characteristics of the quail meat consumer in the Los Olivos district. For this, 328 regular customers from the Cono Norte Zarumilla Caquetá (CONZAC) market were selected, responsible for the purchase of the home, meat consumers, without distinction of gender, over 18 years of age. The questionnaire consisted of 16 questions related to the general data and the behavior of the quail meat consumer. The buyers were merchants-sellers (48,8%), housewives (39,3%) and technicians (11,9%) aged between 36 and 45 years who lived in households consisting of 2 to 5 people (83,3%). Likewise, the respondents stated that they prefer to consume fresh quail meat without fat (52,4%) or with little fat (47,6%), but an amount that does not exceed 2 kilograms (96,4%). The main reason for its consumption was the nutritional properties (72,6%). In conclusion, quail meat does not enjoy popularity among consumers in North Lima, despite its nutritional value.